Simeon the Righteous in rabbinic literature : a legend reinvented - Tropper, Amram D. (Ancient Judaism and early Christianity, 2013)
In Simeon the Righteous in Rabbinic Literature: A Legend Reinvented, Amram Tropper investigates the rabbinic traditions about Simeon the Righteous, a renowned Jewish leader of Second Temple times, and the history of their formation.